Perception of spin and the interception of curved football trajectories - Casanova, R.; Borg, O.; Bootsma, R. J. (Journal of Sports Sciences, 2015)
Using plain white and chequered footballs, we evaluated observers` sensitivity to rotation direction and the effects of ball texture on interceptive behaviour. Experiment 1 demonstrated that the maximal distance at which observers (n = 8) could perceive the direction of ball rotation decreased when rotation frequency increased from 5 to 11 Hz. Detection threshold distances were nevertheless always larger for the chequered (decreasing from 47 to 28 m) than for the white (decreasing from 15 to 11 m) ball. In Experiment 2, participants (n = 7) moved laterally along a goal line to intercept the two balls launched with or without ±4.3 Hz sidespin from a 30-m distance. The chequered ball gave rise to shorter movement initiation times when trajectories curved outward (±6 m arrival positions) or did not curve (±2 m arrival positions). Inward curving trajectories, arriving at the same ±2 m distances from the participants as the non-curving trajectories, evoked initial movements in the wrong direction for both ball types, but the amplitude and duration of these reversal movements were attenuated for the chequered ball. We conclude that the early detection of rotation permitted by the chequered ball allowed modulation of interception behaviour without changing its qualitative characteristics.